IDENTIFIKASI JAMUR PENYEBAB PENYAKIT BUSUK BATANG ANGGREK DAN UJI PATOGENISITASNYA PADA BEBERAPA GENUS ANGGREK - Putra, I Gusti Putu Semara; Wirya, Gusti Ngurah Alit Susanta; Sudiarta, I Putu (AGRICA, 2025)
Plant pests and diseases are barriers to orchid cultivation. These pests and diseases can harm and even destroy cultivated orchids, resulting in losses for producers. This study aims to identify and test fungal infections that cause stem rot in Dendrobium sp., Vanda sp., and Phalaenopsis sp. orchids. The study was carried out at Udayana University's Plant Disease Laboratory, Plant Protection Concentration, Agroecotechnology Study Program, and Faculty of Agriculture. The Fusarium fungus was discovered to be the primary cause of stem rot in Dendrobium sp. marcophyllum orchids after sampling them. The application of Fusarium fungus to three orchid genera, Dendrobium sp., Vanda sp., and Phalaenopsis sp., revealed that Phalaenopsis sp. orchids experienced a significant increase in infection percentage, beginning at 20% in the first week and peaking at 70% in the fifth week, indicating a high susceptibility to the disease. Meanwhile, Dendrobium sp. showed a steadier infection rate, beginning at 10% in the first week and progressively growing to 40% by the fifth week. Vanda sp. exhibited the lowest infection rate, rising from 10% in the first week to 20% by the fifth week, demonstrating a significantly greater resistance than the other two species.